Pemberdaya Penetapan Harga Pokok Penjualan kepada Pelaku UMKM dalam Meningkatkan Laba - Iskandar, Diah; Wahyudi, Sely Megawati (Neolectura, 2024)
The existence of MSMEs in the Meruya Utara Village, Kembangan District, West Jakarta, there are 1249 MSMEs, there are 30 MSMEs assisted by the PKK, Meruya Utara Village looks active. From monitoring in the field, it is known that various types of MSME businesses have problems (1) lacking knowledge in determining the cost of goods sold, (2) determining selling prices based on increases in market prices when purchasing merchandise, (3) and knowledge of preparing profit reports. losses are still very minimal. This makes us, the community service team from the Bachelor of Accounting study program, Faculty of Economics and Business, Mercu Buana University very interested in providing community service to MSMEs in the North Meruya Village, Kembangan District, West Jakarta to increase knowledge in determining the cost of goods sold to calculate business profits. support business sustainability. Potential that can be developed includes the availability of PKK mothers and PKK-assisted MSMEs who are active, have high awareness of entrepreneurship, and are willing to participate as Empowerment participants. Thus, this activity is designed to empower the people of Meruya Utara Subdistrict to become familiar with the concept of Production Costs, calculate the Cost of Goods Sold and prepare profit and loss reports to support business sustainability. Specifically, the solution offered by this activity consists of (1) designing a cost of goods sold report template, (2) training in determining the cost of goods sold, and (3) preparing a Profit and Loss report. The urgency of community empowerment through training in calculating the cost of goods sold, calculating selling prices and preparing profit and loss reports. The aim of this community partnership empowerment activity was formulated in line with the UMB Institute for Research and Community Service program, namely that lecturers and students were jointly involved in empowering partner communities in increasing knowledge of MSMEs in determining the Cost of Goods Sold, compiling profit and loss reports for MSMEs in Meruya Utara District. . The outputs of this community partnership empowerment program include (1) increasing knowledge of determining COGS and skills in calculating COGS (2) increasing community knowledge and skills in preparing Profit and Loss Reports (3) Journal publications, (4) mass media publications, (5) YouTube videos.